Correlacion Entre La Temperatura Superficial Del Sensor Modis Y La Temperatura Media Del Aire En El Departamento De La Guajira, Colombia (2021)
Low density of meteorological stations in La Guajira state causes a deficit of up-to-date and highprecision climate information in most of the remote areas on the region. Data obtained from remote sensors, due to their spatial continuity, can help to improve estimations of this climate information. Therefore, the objective of this document is to determine and evaluate the correlation that exists between maximum and minimum air temperature and daytime and nighttime land surface temperature of MODIS sensor in La Guajira state. In order to do this, stations and sensor data available in the region were extracted in the period between January 1, 2015 and December 31, 2019. From these data, linear regressions were performed in each station and correlation of the information was determined. The results yielded correlations greater than 0.50 between Tamax and daytime surface temperature. For Tamin measurements and nighttime surface temperature, were obtained correlations less than 0.60 in almost all stations. Mixed data showed very good correlations, obtaining values higher than 0.85. These results lead to the conclusion that the determination of the maximum and minimum air temperature from land surface temperature of MODIS sensor has not a good fit with in situ measurements